Multicyclic peptides as scaffolds for the development of tumor targeting agents - Loktev, Anastasia; Haberkorn, Uwe; Mier, Walter (Current medicinal chemistry, 2017)
The lack of specificity of traditional cytotoxic drugs triggers the development of anticancer agents with high selectivity to tumor-specific proteins. The ...